LITERACY AND RISK MANAGEMENT ON A PERSON'S LEADERSHIP SKILL IN ENTREPRENEURSHIP - Soegoto, Eddy Soeryanto; Luckyardi, Senny; Albar, Chepi Nur; Saputra, Herry; Hayati, Euis Neni (Faculty of Economics and Business, University of Pasundan, 2023)
The purpose of this study is to investigate the impact of literacy and risk management on a person's leadership skill in relation to entrepreneurship. This research approach employs quantitative analysis through deduction by statistically calculating a questionnaire that was distributed to 280 prospective entrepreneur and recent graduates. According to the findings, literacy and risk management variables have a major influence on leadership of an entrepreneur in a comprehensive manner, either partially or impartially. As a result, in entrepreneurship, it is vital to equalize these qualities in order to promote individual leadership, which will benefit a good corporate culture. In conclusion, entrepreneurial skill must focus on the development of the hard skill and soft skill including literacy and risk management that will give long-term benefits in order to maintain a healthy and friendly work culture.